A nautiloid from Middle Eocene beds at Grdoselo in Istria, Croatia - Mikuž, Vasja (Geologija, 2009)
Treated are remains of a stone core of phragmocone of an Eocene nautiloid of species Aturia cf. ziczac (Sowerby, 1812) from Grdoselo in central Istria, western Croatia. Remains of Aturia occur in a calcareous sandstone horizon of the Pazin flysch basin megasequence. In these beds occur abundant sea urchins of genera Ecinolampas and Cyclaster, and much less frequent specimens of genera Macropneustes and Conoclypus. Of mollusks are normally found only their stone cores. The relatively modest diversity of sea urchins, high numbers of individual species and total absence of corals might indicate that organisms of this locality most probably remained near their original living environment, without a sign of allochthonicity.